Images and contexts the historiography of science and modernity in India - Raina, Dhruv (New Delhi Oxford Oxford University Press, 2003)
This work attempts to situate the historiography of science in India within a social theory of science. It deals with issues such as the paradigm shift within science studies, the move away from a west-centric theory of science, and future trends and possibilities.
E-Book / Zugriff nur im DHI-Lesesaal
Keywords: Naturwissenschaften; Geschichtsschreibung; Indien